Vitamin D status and its determinants in healthy pregnant women living in Switzerland in the first trimester of pregnancy - Cabaset, Sophie (BMC Pregnancy Childbirth, 2019)
OBJECTIVES: Our study aimed at assessing the prevalence and determinants of vitamin D deficiency (25-hydroxy-vitamin D [25(OH)D] < 20 ng/mL) in pregnant women in the first trimester living in Switzerland. METHODS: From September 2014 through December 2015, 204 pregnant women were conveniently recruited during their first clinical appointment at the Clinic of Obstetrics of the University Hospital Zurich (between week 6 and 12 of pregnancy). Blood samples were collected and a questionnaire focusing on lifestyle and skin colour was completed face-to-face with the responsible physician. Logistic regression analyses were performed with vitamin D status as dependent variable. RESULTS: 63.2% of the participating women were vitamin D deficient, and the median vitamin D concentration in the overall sample was 17.1 ng/mL [Q1, Q3: 9.78, 22.3]. The highest proportions of vitamin D deficiency were detected in women originating from Africa and Middle East (91.4% deficient, median vitamin D concentration of 10.7 ng/mL [Q1, Q3: 6.55, 14.45]) and from South-East Asia/Pacific (88.5% deficient, median vitamin D concentration of 8.4 ng/mL [Q1, Q3: 6.10, 14.88]). Multivariable logistic regression showed that significant risk factors of vitamin D deficiency were country of origin (women born in Switzerland and Germany had a lower risk than women born in other countries), smoking status (lower risk for former smokers) and intake of vitamin D supplements. CONCLUSIONS: Our results confirm a high prevalence of vitamin D deficiency in this Swiss cohort, in particular in women coming from Asian and African countries, and underline the importance of appropriate counseling and vitamin D supplementation in early pregnancy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12884-018-2150-1) contains supplementary material, which is available to authorized users.